Urban development and (un) sustainable cities: challenges for coexistence - Leme Garcez, María Cecilia (2021)
Social care and spaces for healthy coexistence are essential characteristics for fair and equitable urban development in large cities. The objective of this study is to carry out a theoretical and analytical approach to urban development in Latin America, and to present some critical perspectives of development models that are restricted to economic growth goals, making a healthy coexistence in large cities unfeasible, among people and with the environment. Methodologically, the study assumes a qualitative, bibliographic, documentary and social approach.